(untitled) (Italiano LinguaDue, 2018)
L’articolo si sofferma sui servigi che può rendere al traduttore un buon dizionario attraverso le marche d’uso. Si esamina un campione costituito da parole del lessico “elevato” e “regionale” e se ne verifica l’effettiva circolazione attraverso corpora di testi letterari e giornalistici. From literary terms to regionalisms. The dictionary in the hands of the translator The article focuses on the services that can a good dictionary offer translators through labels. A sample of words from a “high” and a “regional” lexicon is examined and the actual use, in literary and journalistic texts, is verified.